COASTAL INLAND COMMUNITY KNOWLEDGE ABOUT ISLAMIC BANKING PRODUCTS (CASE STUDY OF REMBAYAN VILLAGE, WEST KUTAI REGENCY) - Nur Shidik; Darmawati Darmawati; Kokom Komariah (Indonesian Scientific Journal of Islamic Finance, 2026)
The development of Islamic banking in Indonesia shows positive growth, but public literacy and understanding of Islamic banking products remains relatively low, particularly in rural and remote areas. This study aims to analyze the level of public knowledge of Islamic banking products in Rembayan Village, Mook Manaar Bulatn District, West Kutai Regency, and identify influencing factors. The study employed a qualitative descriptive approach, with data collection techniques including in-depth interviews, non-participant observation, and documentation. Nine informants were selected using a purposive sampling technique. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that public knowledge of Islamic banking products is still at the "know" stage, meaning they are only familiar with the term "Islamic banking" and the concept of being free from interest (riba) without a thorough understanding of the product types, mechanisms, and benefits. Factors influencing public knowledge include education level, experience, access to information, economic conditions, and social environment. The dominant factors contributing to this low level of public knowledge are limited access to information and minimal experience interacting with Islamic financial institutions. Supporting factors include strong religious values ”‹”‹in the community, high interest in Islamic banking, and close social ties. Meanwhile, inhibiting factors include limited socialization of Islamic banking institutions, low levels of education, limited physical and digital infrastructure, and the lack of Islamic bank offices in the research area. This study concludes that although public awareness of Islamic banking products remains low, there is significant potential to increase Islamic financial literacy and inclusion through ongoing educational programs, expanded service access, improved digital infrastructure, and strengthened community-based outreach activities.